2022
DOI: 10.3390/ijms23031572
|View full text |Cite
|
Sign up to set email alerts
|

Non-TZF Transcriptional Activator AtC3H12 Negatively Affects Seed Germination and Seedling Development in Arabidopsis

Abstract: CCCH zinc finger proteins are a large protein family and are classified as either tandem CCCH zinc finger (TZF) or non-TZF proteins. The roles of TZF genes in several plants have been well determined, whereas the functions of many non-TZF genes in plants remain uncharacterized. Herein, we describe biological and molecular functions of AtC3H12, an Arabidopsis non-TZF protein containing three CCCH zinc finger motifs. AtC3H12 has orthologs in several plant species but has no paralog in Arabidopsis. AtC3H12-overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…In this study, we observed the regulatory effect of FoDbp40 on ICL expression (Figure 4) and demonstrated that this regulatory effect is achieved at the transcriptional level by acting on the promoter region of ICL (Figure 5). Additionally, we observed the FoDbp40 protein to localize in the nucleus (Figure 6) in line with the bioinformatic analysis (Supplementary Figure S5), which is similar to other known CCCH zinc finger protein transcription factors, including C3H12 and SAW1 (Wang et al, 2020;Seok et al, 2022). Our results indicate that FoDbp40 is a novel transcriptional regulator that can affect the expression and activity of ICL.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, we observed the regulatory effect of FoDbp40 on ICL expression (Figure 4) and demonstrated that this regulatory effect is achieved at the transcriptional level by acting on the promoter region of ICL (Figure 5). Additionally, we observed the FoDbp40 protein to localize in the nucleus (Figure 6) in line with the bioinformatic analysis (Supplementary Figure S5), which is similar to other known CCCH zinc finger protein transcription factors, including C3H12 and SAW1 (Wang et al, 2020;Seok et al, 2022). Our results indicate that FoDbp40 is a novel transcriptional regulator that can affect the expression and activity of ICL.…”
Section: Discussionsupporting
confidence: 84%